Композитні системи медичного призначення, створені на основі гідрофобного кремнезему - Туров, В. В.; Горбик, П. П.; Крупська, Т. В.; Туранська, С. П.; Чехун, В. Ф.; Лук'янова, Н. Ю. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2021)
Composite systems with certain cytotoxic (AM1/lectin) and adsorption (AM1/gelatin) activity have been developed on the basis of methyl silica and protein molecules – lectin and gelatin. For both types of composites, mechanisms of water binding to the surface and methods of transferring of hydrophobic materials into the aquatic environment have been investigated. The state of interfacial water in air, organic and acid media was studied. It has been found that the presence of a hydrophobic component in composites stabilizes of surface water in a weakly associated state, when a significant part of water molecules does not form hydrogen bonds. Liquid hydrophobic medium enhances this effect, and the strong acid (trifluoroacetic), added to it, promotes the transition of water to a strongly associated state. It has been shown that the redistribution of water in the interparticle intervals of AM1 with protein molecules immobilized on their surface changes under the influence of mechanical loads. Mechanoactivated samples are characterized by the possibility of water penetration into the spaces between the primary particles of methyl silica. It has been shown that immobilization of lectin on the surface of AM1 is accompanied by an increase in the interfacial energy gS from 4.1 to 5.2 J/g. This is due to an increase in the concentration of strongly bound water. If we analyze the changes in the distributions of radii R of the clusters of adsorbed water, we can state that in the water adsorbed by native lectin molecules, there are two main maxima at R = 1 and 3 nm. In the immobilized state, the maximum at R = 1 nm is present in both types of water (of different order), but the second maximum is observed only for more ordered associates.